Axial compressive behavior of damaged steel and GFRP bars reinforced concrete columns retrofitted with CFRP laminates. (15th February 2021) - Aslam, Hafiz Muhammad Usman; Khan, Qaiser uz Zaman; Sami, Abdul; Raza, Ali
Abstract: In reinforced concrete (RC) structures, Glass Fiber Reinforced Polymer (GFRP) bars have gained wide acceptance as an alternative to steel bars in coastal and corrosive environments. The majority of studies focused on the axial compressive behavior of undamaged GFRP bars RC columns, comprehensive research on the axial compressive behavior of retrofitted GFRP bars RC has not been conducted because of the limitations of available design codes. This study investigates the axial compressive behavior of damaged GFRP reinforced columns confined with the carbon-FRP (CFRP) sheet. A total of 14 short circular RC columns were fabricated. Seven columns were reinforced with GFRP bars and the remaining seven columns were reinforced with steel bars. Firstly, all the columns were tested under different axial compression conditions until a 35% drop in the peak strength and then these columns were retrofitted with CFRP fabric. The test parameters comprise of testing retrofitted columns under concentric and eccentric loadings. The influence of these parameters on the mode of failure and the ultimate load and displacement conditions of the retrofitted specimens were carefully analyzed. The results revealed that the externally bonded CFRP technique can significantly improve the ultimate axial strength and displacement capacities of damaged GFRP reinforced columns.